How to promote socio-environmental activism? An educational proposal based on transformative learning and media literacy - Varela-Losada, Mercedes; Lorenzo-Rial, María A.; Pérez-Rodríguez, Uxío; Agrelo-Costas, M. Eulalia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Nowadays, there is a need for educational proposals that promote Sustainability through digital activism. The objective of this study was to evaluate the mobilization of teachers’ digital competences through the creation of storytelling about Fast Fashion. Its analysis showed how these experiences can foster the development of skills in communication and collaboration, such as participation in the creation of content, online citizen participation or the ability to share content. The videos created relate everyday actions with socio-environmental consequences and call for a transition towards conscious consumption, showing their creative and inspirational potential.